Implementasi Port Knocking Untuk Keamanan Jaringan Komputer Dengan Metode Demilitarized Zone - Saputro, Andik; Saputro, Daniel Tunggono; Remawat, Dwi (Politeknik Indonusa Surakarta, 2022)
Network security is very vital for a computer network. Weaknesses in computer networks if not protected will cause losses in the form of loss of data or files, damage to server systems, not optimally serving users or even loss of valuable institutional assets. During this pandemic, all teaching and learning activities and exams are carried out online. With the online exam, SMAN 5 Surakarta provides a special server to be provided to students. On the other hand, the server must be accessible online while this can trigger various attacks on the server and it is possible to attack the server via the server IP and port which can result in leaking of confidential data, questions to be tested and data from participants or even these attacks allow the server down. Knowing how to secure a network using DMZ (demilitarized zone) and Port Knocking is the goal of the research. The most frequently used attacks are Port Scanning and DDoS (Distributed Denial of Service). Port Scanning is the initial stage to detect open ports. Whereas DDoS is a DoS attack that utilizes multiple distributed attack resources. Typically, attackers use a large number of controlled bots (host computers/daemons, also referred to as zombies) distributed across several different locations to launch a large number of DoS attacks against a single target or multiple targets. For this reason, network security techniques are needed that can ward off the threat of these attacks or minimize the threat of attacks that can enter the network system. In this study, the DMZ (demilitarized zone) technique was implemented to access the local server so that it could be accessed from outside safely and using the Port Knocking technique to open filtered access ports.